Antibody recognition of aberrant glycosylation on the surface of cancer cells. (June 2017) - Soliman, Caroline; Yuriev, Elizabeth; Ramsland, Paul A
Graphical abstract: Highlights: Several carbohydrate antigens are being considered for antibody-based cancer immunotherapies. Crystallography has revealed many aspects of antibody recognition of tumor-associated glycans. Computational and binding data has been key to dissecting several antibody–glycan interactions. The structural basis for antibody activity at the surface of cancer cells requires further study. Abstract : Carbohydrate-binding antibodies and carbohydrate-based vaccines are being actively pursued as targeted immunotherapies for a broad range of cancers. Recognition of tumor-associated carbohydrates (glycans) by antibodies is predominantly towards terminal epitopes on glycoproteins and glycolipids on the surface of cancer cells. Crystallography along with complementary experimental and computational methods have been extensively used to dissect antibody recognition of glycan epitopes commonly found in cancer. We provide an overview of the structural biology of antibody recognition of tumor-associated glycans and propose potential rearrangements of these targets in the membrane that could dictate the complex biological activities of these antibodies against cancer cells.